Opting or Not Opting to Share Income Tax Information with the Census: Does it Affect Research Findings? - Brochu, Pierre; Morin, Louis-Philippe; Billette, Jean-Michel (Université d'Ottawa | University of Ottawa, 2013)
This paper examines the implication of the decision to give 2006 Census respondent the option of letting Statistics Canada access their income tax files rather than answering income related questions directly. We find that giving respondents the option to share their income tax files (or not) adds a confounding factor when it comes to measuring family income inequality, particularly for the bottom tail of the distribution. The consent decision does not, however, materially affect the estimation of standard wage equations. / Ce document examine l’implication de la décision de donner aux répondants du recensement de 2006 l’option de donner permission à Statistique Canada de consulter leur déclaration d’impôt plutôt que de répondre directement aux questions portant sur le revenu. Nous trouvons que donner l’option aux répondants de partager (ou pas) leur rapport d’impôt ajoute un facteur de confusion lorsqu’il s’agit de mesurer l’inégalité du revenu des familles, particulièrement dans le bas de la distribution. Toutefois, la décision de consentement ne touche pas de façon importante l’estimation des équations salariales standard.
Keywords: Census; record linking; consent; income inequality; wage equation; recensement; couplage de données; consentement; inégalités de revenu; équation de salaire